COBERTURA VEGETAL, ESPAÇOS LIVRES E ÁREAS VERDES EM PONTA GROSSA-PR: MAPEAMENTO, TIPIFICAÇÃO E ANÁLISE - Queiroz, Dulcina Aquino Hernandez de Oliveira (2014)
The evaluation of vegetal coverage, open spaces and green areas play a fundamental role for the planning and development of cities like Ponta Grossa. It enables both to highlight the effectiveness and identify the weakness related to those elements on the urban space. In this sense, this thesis proposes to understand the open spaces, green areas and spatial dynamics of the vegetal coverage of the Ponta Grossa's urban area.To accomplish this, it recurs to bibliographical review, data generation and to identify both tipology and spatialization of green areas as well as to evaluate its availability to the public. The thesis classifies Ponta Grossa's vegetation and analysis its distribution along 2004. In this context, it quantifies open spaces and green areas per borough by means of geotechnologies. In the aforementioned year, Ponta Grossa had 172,59 km² of urban area and 266,683 habitants. In turn, vegetal coverage had 49% of the entire urban area and presented an index of 319,3 m²/habitant. Finally, open space had an area of 2,5% composed by 230 spaces, they are: 132 sport fields, 63 public squares, 4 parks, 6 cemeteries and 8 clubs; with an index of 16,4 m²/habitant. In summary, in spite of the fact the numeric results for each category can be classified as satisfactory, their distribution can not and might impairing their effectiveness.